Approximation of capacities with additive measures - Nykyforchyn, O.R.; Hlushak, I.D. (Carpathian Mathematical Publications, 2017)
For a space of non-additive regular measures on a metric compactum with the Prokhorov-style metric, it is shown that the problem of approximation of arbitrary measure with an additive measure on a fixed finite subspace reduces to linear optimization problem with parameters dependent on the values of the measure on a finite number of sets. An algorithm for such an approximation, which is more efficient than the straighforward usage of simplex method, is presented.